The apolipoprotein E ε4 allele selectively increases the risk of frontotemporal lobar degeneration in males. Issue 2 (17th January 2006) - Srinivasan, R; Davidson, Y; Gibbons, L; Payton, A; Richardson, A M T; Varma, A; Julien, C; Stopford, C; Thompson, J; Horan, M A; Pendleton, N; Pickering-Brown, S M; et al.
Abstract : Objective: To determine whether polymorphic variations in the apolipoprotein E gene ( APOE ) are associated with increased risk of frontotemporal lobar degeneration (FTLD) when mutation in tau gene is absent. Methods: The APOE gene was genotyped by polymerase chain reaction from DNA routinely extracted from blood or brain tissues. The APOE ε4 allele frequency in 198 patients with FTLD not associated with mutations in tau gene was compared with that of a control group of 756 normal individuals drawn from the same geographical region. Analyses were done according to clinical subtype or sex. Results: The APOE ε4 allele frequency (19.4%) was increased (p = 0.01) in FTLD v the whole control group (14.1%), while the APOE ε2 allele frequency in FTLD (6.5%) was slightly lower than in controls (8.0%) (NS). The APOE ε4 allele frequency in men with FTLD (22.3%) was greater (p = 0.002) than in male controls (12.3%); the frequency in women (16.3%) was similar to that in female controls (14.8%) (NS). The APOE ε2 allele frequency in men with FTLD was 4.9% while in male controls it was 9.5% (p = 0.06), but there was no difference in women (7.5% v 7.9%, NS). Neither the APOE ε2 nor APOE ε4 allele frequency varied significantly between any of the clinical subtypes. Conclusions: In FTLD not associated with mutations in tau gene, possession of APOE ε4 allele in men roughly doubles the chances of developing disease, whereas this has no impact upon disease risk in women.